Математическое моделирование и оптимизация в лесопромышленном комплексе - Muratov A. I. (Innovative technologis in science and education, 2017)
вased on the experience of Petrozavodsk University, it is shown that the competitiveness of universities in the IT-goods and IT-services market in the timber industry complex can be ensured by mathematical modeling and solving optimization problems.
Keywords: математическое моделирование; оптимизация; лесопромышленный комплекс; optimization; Mathematical modeling; forestry complex; the market of IT-goods and IT-services; рынок IT-товаров; рынок IT-услуг